Factors influencing purchasing decision on Telkomsel providers in Solo Raya - Fernandita Khusnul Khotimah; Putri Maisara (Universitas Pendidikan Nasional, 2023)
The article explored the influence of product quality, brand image, and Word of Mouth on purchasing decisions for Telkomsel provider cards in Solo Raya, Indonesia. Drawing upon literature reviews and quantitative methods, the study analyzed data from 105 respondents using validity, reliability, normality, multicollinearity, heteroscedasticity tests, as well as multiple linear regression and t-tests. Findings indicated that while product quality positively impacted purchasing decisions, it was not statistically significant. Conversely, brand image and Word of Mouth significantly influenced consumer choices. The study concluded by recommending strategies for Telkomsel to enhance product quality, maintain brand integrity, and leverage positive Word of Mouth marketing to improve sales. Future research was suggested to expand the sample size and include additional variables for a comprehensive understanding of consumer behavior in Telkomsel card purchases.